Penguatan Hukum Ekonomi Syariah pada Lembaga Keuangan Berdasarkan UU Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan - Tegar Wahyudi; Adik Sukmawati; Ulfah Dwi Rahmawati; Fahmi Fairuzzaman (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
There are three objectives in this research, namely to find out the concept of sharia economic law in financial institutions in terms of Law Number 21 of 2011 concerning OJK (Financial Services Authority), strengthening sharia economic law within the Financial Services Authority, and handling sharia economic law problems. by the Financial Services Authority. In this study through the stages of problem identification, preparation of activity proposals, and program implementation. By using a normative legal research method (juridical-normative) with a statutory approach and a concept approach. In terms of data collection, library research is the technique used in collecting our research data for content analysis in order to obtain normative data. The concept of sharia economic law at the Financial Services Authority is related to sharia economics, the strengthening of sharia economic law is contained in Law Number 21 of 2011 concerning the Financial Services Authority, if there are sharia banking problems this can be resolved by using a court or through an institution organized by the Authority. Financial Services, namely Alternative Dispute Resolution Institutions.